Quercetin Regulates Calcium and Phosphorus Metabolism Through the Wnt Signaling Pathway in Broilers - Wang, Bo; Wang, Shanshan; Ding, Manyi; Lu, Han; Wu, Hao; Li, Yao (Frontiers in Veterinary Science, 2022)
This study was intended to explore the effect and mechanism of different doses of dietary quercetin on calcium and phosphorus metabolism to provide experimental basis for reducing leg disease in broilers. 480 one-day-old healthy Arbor Acre broilers were randomly allotted to 4 dietary treatments (0, 0.02%, 0.04%, 0.06%) for 42 days. Compared with control, 0.06% quercetin significantly increased the unit weight and the relative weight of tibia (P<0.05). Meanwhile, phosphorus content and bone mineral density (BMD) were significantly increased by 0.06% dietary quercetin supplementation in tibia (P<0.05), ash of tibia was significantly increased by 0.04% and 0.06% quercetin (P<0.05). In addition, 0.06% quercetin significantly increased content of serum calcium-binding protein (CB), estradiol (E2), osteocalcin (OC), alkaline phosphatase (ALP) and calcitonin (CT) (P<0.05), 0.04% quercetin significantly increased 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) (P<0.05) content in serum. 0.02% and 0.06% quercetin significantly decreased parathyroid (PTH) (P<0.05) content in serum. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes (KEGG) enrichment analysis showed that Wnt signaling pathway was a key signal pathway of calcium and phosphorus metabolism in broilers which significantly regulated by quercetin. The Real-Time quantitative PCR (RT-qPCR) of 7 differentially expressed genes (DEGs) were basically the same as transcriptome sequencing. In conclusion, 0.06% quercetin improved calcium and phosphorus metabolism by regulating the wnt signaling pathway in broilers.